2023
DOI: 10.1002/epi4.12683
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter cohort study of possible psychogenic nonepileptic seizure cases—Results at 1‐year follow‐up examinations

Abstract: Objective: The primary purpose of this prospective multicenter study was to examine clinical and demographic feature differences according to the diagnostic level of psychogenic nonepileptic seizures (PNES) and then clarify whether prognosis may also differ accordingly.Methods: Two hundred forty-two consecutive patients strongly suspected of having PNES attacks were invited to participate, of whom 52 did not consent or contact was lost. At the 1-year follow-up examination, PNES diagnosis was reconsidered in ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…40 The risk of misdiagnosing dissociative seizures based on detailed history and interictal EEG alone was less than 5% in a cohort study of 190 patients. 41 An audit of inpatients who received a first diagnosis of dissociative seizures at our department showed that in none of the cases with available long-term follow-up was the diagnosis overturned. 42…”
Section: Limitationsmentioning
confidence: 93%
“…40 The risk of misdiagnosing dissociative seizures based on detailed history and interictal EEG alone was less than 5% in a cohort study of 190 patients. 41 An audit of inpatients who received a first diagnosis of dissociative seizures at our department showed that in none of the cases with available long-term follow-up was the diagnosis overturned. 42…”
Section: Limitationsmentioning
confidence: 93%